2020
DOI: 10.3390/su12218882
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Organizations’ Resistance to the Adoption of Blockchain Technology in Supply Networks

Abstract: From a supply chain perspective, new technologies such as blockchain can improve the efficiency and competitiveness of logistics and increase customer satisfaction. Although blockchain technology has been lauded as a way for firms to build sustainable supply chain networks, the rate of acceptance of this technology remains low. Therefore, this study seeks to identify the factors that discourage firms from merging blockchain with the supply chain. Instead of providing further reasons for adopting blockchain tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 88 publications
2
74
1
1
Order By: Relevance
“…Furthermore, the environmental context refers to the regulatory environment, market factors, and competitors. e extant literature shows the use of the TOE framework for examining factors of blockchain technology adoption [8,9,13,45].…”
Section: Research Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the environmental context refers to the regulatory environment, market factors, and competitors. e extant literature shows the use of the TOE framework for examining factors of blockchain technology adoption [8,9,13,45].…”
Section: Research Frameworkmentioning
confidence: 99%
“…Furthermore, compatibility of technology also involves consideration of organizational culture [52] and the available technology infrastructure [53]. It is easier for an organization to apply blockchain technology to its supply chains if it has a high compatibility level [9]. e existing studies have confirmed that the compatibility of blockchain technology positively influences the intention to adopt it in supply chains by the organizations [13,51,54].…”
Section: Hypothesis Development-innovation Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stuart Haber and W. Scott Stornetta introduced the first idea of blockchain in a paper entitled "How to time stamp a Digital Document" in 1991 [2], their intention was to develop a system based on documented timestamps that could not be altered or tampered with. Being the Internet was immature, Heber and Store's idea did not reach the public about cryptographic trust between parties [3]. Blockchain appeared back in 2008 as an incredibly promising technology after Satoshi Nakamoto introduced Bitcoin as a cryptocurrency in a paper titled "A peer-to-peer electronic cash system" ] 4 [ .…”
Section: Introductionmentioning
confidence: 99%